Enhancing Academic Mobility and Innovation in Sierra Leone’s Higher Education: A National Policy Proposal for Diversified Tuition Waivers across Universities - DUMBUYA, Emmanuel (Journal of Research in Educational Sciences; Vol 16 No 1 (2025): JRES, Volume XVI, Issue 1(19), Summer 2025, 2025)
This article critically examines the current practice of tuition waivers for academic staff pursuing higher degrees within their home institutions in Sierra Leone’s universities. While commendable efforts by university leadership, such as the University of Sierra Leone’s Vice Chancellor’s call for staff to seek postgraduate and doctoral studies beyond their institutions, aim to foster academic diversity and innovation, the existing tuition waiver policies remain institution-bound. This paper argues for a transformative policy reform to diversify and extend tuition waivers across universities nationally, enabling academic staff to study at any accredited institution within Sierra Leone with financial support. Such a policy would mitigate academic inbreeding, promote cross-institutional collaboration, and enhance the overall quality and global competitiveness of Sierra Leone’s higher education system. Drawing on theoretical frameworks of academic mobility and institutional innovation, this policy article outlines the rationale, potential benefits, implementation challenges, and strategic recommendations for stakeholders in Sierra Leone’s higher education sector.